Model and calculation method of frost heaving stress of stagnant water of tunnel in seasonally frozen area. Issue 1 (1st January 2021) - Cui, Guangyao; Ma, Jianfei; Wang, Xuelai; Wang, Daoyuan
Abstract: The frost heave caused by the stagnant water may seriously threaten tunnels' operation safety and service life in seasonally frozen areas. This paper aims to put forward new insights for the accurate evaluation of the frost heaving stress and the prevention of frost damage in seasonally frozen-region tunnels. Firstly, based on the local frost theory and local deformation theory, a new calculation model of the frost heaving stress caused by stagnant water is established. In this model, the space of stagnant water is simplified as the three-axis semi-ellipsoid, which is more in line with the actual situation. Then, the rationality of the new calculation model was verified by comparing it with the results of numerical analysis and previous studies. Finally, the effects of the crucial parameters in the calculation model were also conducted by the univariate method. The results show that the theoretical model is in good agreement with the numerical simulation. The theoretical analysis exhibits the more conservative results, which may provide a practical approach for damage assessments and frost preventions in the case of a lack of observed in-site data. Besides, some significant suggestions about the construction and design of seasonally frozen-region tunnels are obtained.